2022
DOI: 10.1007/978-3-031-06413-5_12
|View full text |Cite|
|
Sign up to set email alerts
|

Pulse Oximetry: The Working Principle, Signal Formation, and Applications

Abstract: Pulse oximeters are routinely used in various medical-grade and consumer-grade applications. They can be used to estimate, for example, blood oxygen saturation, autonomic nervous system activity and cardiac function, blood pressure, sleep quality, and recovery through the recording of photoplethysmography signal. Medical-grade devices often record red and infra-red light-based photoplethysmography signals while smartwatches and other consumer-grade devices usually rely on a green light. At its simplest, a puls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 70 publications
0
0
0
Order By: Relevance
“…A pulse oximeter can detect the oxygen saturation of haemoglobin quickly and in an accurate and reliable way. Pulse oximetry combines oximetry and plethysmography to measure SPO 2 non-invasively [ 21 ]. According to Lambert Beer’s law, oxygenated and reduced hemoglobin absorb red and infrared light differently.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A pulse oximeter can detect the oxygen saturation of haemoglobin quickly and in an accurate and reliable way. Pulse oximetry combines oximetry and plethysmography to measure SPO 2 non-invasively [ 21 ]. According to Lambert Beer’s law, oxygenated and reduced hemoglobin absorb red and infrared light differently.…”
Section: Methodsmentioning
confidence: 99%
“…Oxyhaemoglobin absorbs more infrared light, whereas reduced haemoglobin absorbs more red light. The rate of absorption at the red and infrared wavelengths is analyzed by oximetry to give the oxygen saturation of arterial pulsations [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Clinicians are usually concerned about authenticity of portable devices. Although these devices undergo a standardization process before to being marketed, it has been observed that there is frequently a level of discrepancy in the results or readings in real clinical scenarios 8 . With this background, we conducted this study to compare the oxygen saturation values obtained from conventional and portable fingertip pulse oximeters.…”
Section: Introductionmentioning
confidence: 99%
“…This includes intensive care units, surgical theaters, recovery rooms, emergency departments, and general hospital wards. It is used to assess any patient's oxygenation, determine the need for additional oxygen, and detect life-threatening conditions in newborns and premature infants [4][5][6][7]. Additionally, pulse oximeters find utility in healthy people in the training and testing of pilots, firefighters, military personnel, professional athletes, and mountain climbers [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%